Justice in Judicial and Non-Judicial Practice in the Administration of the Russian Labor Law: Problems and Prospects - VOLKOVA, Victoria V.; SAPFIROVA, Apollinariya A.; PETRUSHKINA, Anna V. (Journal of Advanced Research in Law and Economics, 2017)
Justice is an important component of a regulatory act. Unfortunately, issues related to legal justice and its duality in developing countries, such as Russia, are understudied. Therefore, this research investigates the regulations of the labor law from the perspective of justice and the practice of their administration. The research also analyzes the legislation of the Russian Federation and court rulings related to labor disputes. The conclusion is that the law can be unjust, but that does not mean that it loses its legal force; hence, justice cannot affect the subject of administration of law with a view to preferring justice to law in case of discrepancies between these two concepts. Theoretical recommendations are given regarding the reformation of the legal framework of the Russian Federation, which will reduce the number of lawsuits related to labor disputes.